2009
DOI: 10.2174/1876397900901010011
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Effluents From Warri Refinery Petrochemical Company WRPC on Water and Soil Qualities of “Contiguous Host” and “Impacted on Communities” of Delta State, Nigeria

Abstract: This study investigated the effect of refinery effluents on different sources of potable water supply in two areas of Niger Delta contiguous host and impacted on communities of Delta State, Nigeria (surface water, shallow well water and borehole water) in Ekpan, its adjoining communities and creeks. Since open and underground water bodies are regarded as final recipient of most environmental pollutant, we sought through the study to provide data on pollutant load of potable water supply of the study area. Cadm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…In Nigeria's Niger Delta Region, and indeed Nigeria, the problem of water resources is the availability of good-quality (potable) water because of environmental pollution and degradation (Efe 2001b); beside this, valuable man-hours and resources are spent traveling long distances fetching water of doubtful quality. Previous studies have shown that water resources in Nigeria are easily contaminated from anthropogenic activities (Orisakwe et al 2001;Ovrawah, and Hymore 2001;Nduka et al 2009). The unregulated discharge of untreated effluents into natural receptors by industries in Nigeria has been reported (Egborge 2000).…”
Section: Introductionmentioning
confidence: 98%
“…In Nigeria's Niger Delta Region, and indeed Nigeria, the problem of water resources is the availability of good-quality (potable) water because of environmental pollution and degradation (Efe 2001b); beside this, valuable man-hours and resources are spent traveling long distances fetching water of doubtful quality. Previous studies have shown that water resources in Nigeria are easily contaminated from anthropogenic activities (Orisakwe et al 2001;Ovrawah, and Hymore 2001;Nduka et al 2009). The unregulated discharge of untreated effluents into natural receptors by industries in Nigeria has been reported (Egborge 2000).…”
Section: Introductionmentioning
confidence: 98%
“…Thus, potential contamination of shallow groundwater with heavy metals from four primary sources have been suggested: oil and gas and related industry activities (Aremu, Olawuyi, Metshitsuka, Sridhar, & Oluwande ,2002;Nduka & Orisakwe, 2007, 2009Emonyan, Akporhonor & Akpoborie, 2008;Etchie, Etchie & Adewuyi, 2011), leachates from unregulated garbage dumps (Akudo, Ozulu & Osogbue , 2010), road wash and storm water runoff (Egboh, Nwajei & Adaikpoh, 2000) and soils (Iwegbue, Nwajei, Ogala, & Overah, 2010). In addition, Olobaniyi and Owoyemi (2004; have also suggested possible chloride enrichment of the underlying aquifer by recharge from the tidal Warri River and its tributary creeks and argue that heavy ground water abstractions in parts of the city are potentially inducing sea water intrusion from the Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, no amphibian eggs/tadpoles or adult forms were encountered inside the mangrove habitats of Ijala-Ikeren wetland. The acidity of water was explained by [6] who investigated the impact of refinery effluents around Warri Refinery and Petrochemical Company (WRPC) on surface waters of the creeks and soil qualities of host communities within and around Ijala-Ikeren wetland, and concluded the change in water pH to be 6.3, while the soil pH was 6.8 in Ijala-Ikeren wetland. This inference may be related to the discharge of these effluents from Warri Refinery and Petrochemical Company (WRPC) into Warri River which feeds the Ijala waters and also crude oil and its fraction seepages from numerous loading and off-loading jetties within the river which finds its way into the creeks in the Ijala-Ikeren wetland.…”
Section: Discussionmentioning
confidence: 99%
“…The Niger Delta biodiversity, including the Ijala-Ikeren wetland is very important for the concomitant presence of rainforests, mangroves, and many endemic flora and fauna, which are affected by oil pollution from oil spills, usually from bunkering and pipeline vandalisation of the petroleum refinery facilities situated less than 2 km to the East of the Ijala-Ikeren Wetland as well as solid waste pollution.Oil pollution and its attendant impact on the creek ecology and the community are highly visible in the mangrove swamps due to proximity of the communities to refinery and oil pipelines criss-crossing the environment. The Ijala-Ikeren wetland has been affected by industrial activities, and pollution and this has affected the water quality in the community, and arthropods (insects) and amphibians [6]. Reported that the physical and sanitary quality of hand-dug well waters from communities around the Warri refinery including Ijala-Ikeren wetland was found slightly acidic at 6.04 and may be attributed to emissions from gas flaring and petroleum refining activities, which is common in the area.…”
mentioning
confidence: 99%
See 1 more Smart Citation